2017
DOI: 10.1111/cup.12981
|View full text |Cite
|
Sign up to set email alerts
|

Superficial papular neuroma: Case series of a new entity

Abstract: We report a small series of benign neural lesions and propose the name "superficial papular neuroma" for this distinct entity. Awareness is important to understand the clinical significance of these lesions and avoid misinterpretation that could lead to overtreatment, unnecessary work-up and increased cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…We observed this feature in 63 (11.3%) plaques. This alteration has also been observed in a cutaneous neural lesion that shows some similarities with the SNP [23].…”
Section:  Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We observed this feature in 63 (11.3%) plaques. This alteration has also been observed in a cutaneous neural lesion that shows some similarities with the SNP [23].…”
Section:  Discussionsupporting
confidence: 59%
“…We observed this feature in 63 (11.3%) plaques. This alteration has also been observed in a cutaneous neural lesion that shows some similarities with the SNP [ 23 ]. The excretory ducts of the minor salivary glands normally empty into the furrows or moats of the papillae.…”
Section: Discussionmentioning
confidence: 56%
“…Superficial papular neuroma (SPN) is a rare, benign cutaneous nerve sheath tumor that was first described by Chen et al 1 Since their collective report of 4 cases, no new cases have been reported. Clinically, SPN appears as a solitary 2–6 mm skin-colored papule resembling a nevus or cyst.…”
Section: Introductionmentioning
confidence: 99%